2019
DOI: 10.3748/wjg.v25.i43.6416
|View full text |Cite
|
Sign up to set email alerts
|

Altered profiles of fecal metabolites correlate with visceral hypersensitivity and may contribute to symptom severity of diarrhea-predominant irritable bowel syndrome

Abstract: BACKGROUNDFecal metabolites are associated with gut visceral sensitivity, mucosal immune function and intestinal barrier function, all of which have critical roles in the pathogenesis of irritable bowel syndrome (IBS). However, the metabolic profile and pathophysiology of IBS are still unclear. We hypothesized that altered profiles of fecal metabolites might be involved in the pathogenesis of IBS with predominant diarrhea (IBS-D).AIMTo investigate the fecal metabolite composition and the role of metabolites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 72 publications
2
22
1
1
Order By: Relevance
“…Reduced amounts of acylcarnitines were associated with a high degree of constipation for IBS patients, supported by previous research linking carnitine deficiency to constipation [ 29 ]. Although clear differences in metabolite concentrations were observed between the two groups, metabolite concentrations could not be correlated with reductions in IBS symptoms, in contrast to the correlation between metabolite concentrations and GI symptoms as have been found in previous cross-sectional studies [ 8 , 9 , 10 ]. In addition, variation in the intervention group was expected as some patients with IBS experience worse symptoms of fat, fiber, and dairy products [ 30 ], food items that were more ingested during the SSRD regime [ 3 , 22 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Reduced amounts of acylcarnitines were associated with a high degree of constipation for IBS patients, supported by previous research linking carnitine deficiency to constipation [ 29 ]. Although clear differences in metabolite concentrations were observed between the two groups, metabolite concentrations could not be correlated with reductions in IBS symptoms, in contrast to the correlation between metabolite concentrations and GI symptoms as have been found in previous cross-sectional studies [ 8 , 9 , 10 ]. In addition, variation in the intervention group was expected as some patients with IBS experience worse symptoms of fat, fiber, and dairy products [ 30 ], food items that were more ingested during the SSRD regime [ 3 , 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…One of the most important treatments is dietary advice with less intake of fermentable carbohydrates [ 2 , 3 ]. In the last years, several studies have found altered metabolite profiles in IBS patients in feces [ 4 , 5 , 6 ] or serum [ 7 ], which correlated with the severity of symptoms and visceral hypersensitivity [ 8 , 9 , 10 ]. Further, metabolite signatures (metabolomics) have been associated with several central sensitivity pain syndromes, including IBS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, numerous studies have addressed the role of gut microbiota in IBS pathophysiology [13][14][15][16]. More recently, reports focusing on intestinal metabolites [17,18], alongside studies integrating the gut microbiome and metabolome [22,24,25], as Significantly enriched biological functions predicted to be associated with changes in metabolites in patients with IBS compared to healthy subjects. The bar plot represents 22 biological functions predicted to be altered in IBS patients with significant activation Z-score > 2 or < −2 identified by IPA core analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have described an altered composition of gut microbiota and metabolites in several diseases of the GI tract such as colorectal cancer and inflammatory bowel disease [11,12]. In addition, IBS has been linked to an unbalanced gut microbiota profile [13][14][15][16] and possibly also to an altered metabolite profile [17,18], with links to GI [17,19] and psychological symptoms [20], at least in subsets of patients. There are also contradictory reports of lower, as well as higher, concentrations of faecal short-chain fatty acids in IBS with diarrhoea (IBS-D) as compared to healthy subjects [21].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier targeted metabolomics studies primarily focused on several categories of metabolites, including SCFAs, amino acids, bile acids, etc. [26,45]. In contrast, non-targeted metabolomics approaches under development collected more detailed and global metabolic profiling data concerning metabolic homeostasis and aberrance [14,19,46,47].…”
Section: Discussionmentioning
confidence: 99%